Secure Complaint Management System against Women Harassment at Workplace Using Blockchain Technology - Md. Mijanur Rahman; Md. Moshiul Azam; Faria Sanjida Chowdhury (International Journal of Electrical and Computer Engineering Systems, 2022)
Since the Industrial era, women are playing a significant role in the workforce to move the world forward. Their increasing contribution in various fields has earned a fortune for the global economy. Despite that, women constantly face more obstacles than men in the workplace. When half of the population are mistreated because of gender inequality, the economy of any nation is supposed to collapse. One of the biggest barriers for women in their careers is workplace harassment. Workplace harassment may include physical, verbal or nonverbal harassment that not only have an adverse effect on a woman's career, mental health and physical health but also organizational reputation. A common way to make a complaint in most organizations is to fill up a complaint form, email or go directly to the competent authority and complain. But victims often hesitate to complain because their identity might get revealed or their documentary evidence might be tampered. As a result, most of the harassers get through very easily. To resolve this problem, this paper presents a blockchain-based anonymous, transparent and secure platform where women can easily complain against their harassers. To keep the platform secure and reliable, a two-level hierarchical model is introduced, where level-1 is the Human Resources (HR) and level-2 is the Higher Authority. In level-1, victims can anonymously complain to HR and in Level-2, victims can complain with their identity revealed to higher authority. This way, the proposed platform ensures women of a healthy work environment and provides all necessary support to stand up against injustice in the workplace.